2015
DOI: 10.1371/journal.pone.0124672
|View full text |Cite
|
Sign up to set email alerts
|

A Global Optimization Approach to Multi-Polarity Sentiment Analysis

Abstract: Following the rapid development of social media, sentiment analysis has become an important social media mining technique. The performance of automatic sentiment analysis primarily depends on feature selection and sentiment classification. While information gain (IG) and support vector machines (SVM) are two important techniques, few studies have optimized both approaches in sentiment analysis. The effectiveness of applying a global optimization approach to sentiment analysis remains unclear. We propose a glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 36 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…This is primarily because such tools are designed for formal medical text only, and are incapable of understanding social media expressions. Unsurprisingly, SVMs have obtained the best performance for a long time and are still very difficult to beat in terms of performance [108,114,117,[134][135][136]. Very recently, deep neural-network-based models have been designed and employed for social media health text classification, with very promising results [137].…”
Section: Content Analysis and Text Classificationmentioning
confidence: 99%
“…This is primarily because such tools are designed for formal medical text only, and are incapable of understanding social media expressions. Unsurprisingly, SVMs have obtained the best performance for a long time and are still very difficult to beat in terms of performance [108,114,117,[134][135][136]. Very recently, deep neural-network-based models have been designed and employed for social media health text classification, with very promising results [137].…”
Section: Content Analysis and Text Classificationmentioning
confidence: 99%
“…The direction of path can be adjusted according to the velocity of each particle based on its own flight experience and the experiences of its companions. The optimal regions of complex search spaces are mined based on this superior strategy through the interaction of individuals in a set of particles [23]. There are four steps within a process period in PSO.…”
Section: Tf Idf Tf T D Idf T  (3)mentioning
confidence: 99%
“…They have compared this approach with NB and Maximum Entropy methods and found that their method gave higher accuracy (0.76) as compared to NB (0.67) and Maxent (0.76) when applied to movie review datasets. Abbasi et.al [9] attempted to do benchmarking of twitter sentiment analysis tools.20 tools were applied to 5 test beds like telecom, [19] tried global optimization approach to multipolarity sentiment analysis. They found that 3-class polarity classification resulted in much lower accuracies as compared to 2-class polarity classification.…”
Section: Supervised Machine Learningmentioning
confidence: 99%
“…They applied this approach to the products like laptops and restaurants from Semeval2014 datasets with precision and recall scores between 82 to 88% with restaurant dataset giving better scores than laptops. Particle swarm optimization algorithm named as PSOGO-senti was developed and applied by Xinmiao et.al[19] specially applied to Chinese sentiment analysis for binary and multi polarity sentiment classification. They found that this algorithm is capable of eliminating redundant and noisy features.…”
mentioning
confidence: 99%